Association of soluble CD40L with short-term and long-term cardiovascular and all-cause mortality: The Ludwigshafen Risk and Cardiovascular Health (LURIC) study. (December 2019) - Gergei, Ingrid; Kälsch, Thorsten; Scharnagl, Hubert; Kleber, Marcus E.; Zirlik, Andreas; März, Winfried; Krämer, Bernhard K.; Kälsch, Anna-Isabelle
Abstract: Background and aims: The CD40 − CD40 Ligand (CD40L) system has an important role in vascular inflammation. For this reason, we assessed the association of soluble CD40L with cardiovascular and all-cause mortality in the Ludwigshafen Risk and Cardiovascular Health (LURIC) study. Methods: Plasma levels of sCD40L were determined in 2759 persons using an enzyme immunoassay. Cox proportional hazard regressions were performed to evaluate the association between plasma concentration of sCD40 ligand and short-term (12 months) and long-term (10 years) mortality. Subpopulation analyses were conducted in seven different risk groups. Cox regression models were adjusted for traditional risk factors. Results: The present study did not reveal significant association between sCD40L plasma levels and all-cause mortality, as well as cardiovascular mortality at one-year follow-up. In selected subgroups only, significant association between elevated sCD40L plasma levels and short-term all-cause and cardiovascular mortality could be observed. With regard to long-term all-cause and cardiovascular mortality analyses, no significant correlation with increased plasma levels of sCD40L could be detected, neither overall nor in any subgroup. Conclusions: Soluble sCD40L is not associated with cardiovascular and all-cause mortality in this large cohort. Only in selected patient subgroups elevated levels of sCD40L correlate with short-term mortality but this correlation disappears in long-term analysis. Graphical abstract: Image 1 Highlights: The association of sCD40L with mortality in the Ludwigshafen Risk and Cardiovascular Health study has been investigated. There was no significant association of sCD40L with long-term cardiovascular mortality and all-cause mortality. No patient subgroup revealed a significant association between sCD40L and long-term all-cause or cardiovascular mortality. No previously published study ever investigated such a large number of patients over such a long follow-up period. Elevated levels of sCD40L seem only to be associated with short-term mortality in selected patient groups.